Value of energy storage for transmission investments. (April 2019) - Khastieva, Dina; Hesamzadeh, Mohammad Reza; Vogelsang, Ingo; Rosellón, Juan; Amelin, Mikael
Abstract: This paper investigates joint investment planning of transmission lines and energy storage. Energy storage can be seen as a complement to transmission infrastructure and can be used for transmission deferral. On the other hand, under certain conditions, when the expected profit of both sectors depends on congestion in the system, transmission and energy storage can be seen as competitors. The transmission sector is in this study assumed to be a natural monopoly and operation and planning of transmission lines is performed by an independent company whereas the energy storage owner company operates and invests under competitive market rules. Three main questions are addressed in this paper. First of all, will additional energy storage capacity contribute to the growth of social welfare? Second, how will incentive regulation of the transmission network affect the need for energy storage? Third, how will the choice of incentive regulation affect the value of energy storage. This paper first provides an overview of incentive regulation which can be applied to transmission investments. Then case studies based on a 6-node power system network and the IEEE 118-node system are proposed in order to answer the aforementioned questions. The results of the case studies show that energy storage investments complement transmission expansion and contribute to higher social welfare values. The benefits from energy storage investments are significantly higher under two investigated incentive regulations as compared to the case without incentive regulation. Thus, the transmission investment planning process should consider energy storage options. Highlights: Several incentive mechanisms are reviewed and compared. Incentive regulations are applied to transmission investment problem. Bilevel stochastic MINLP models are proposed. Proposed models simulate joint energy storage and transmission investment problem. Incentive regulations can support socially optimal investment decisions.